Optical gain tuning within IR region in type-II In0.5Ga0.5As0.8P0.2/GaAs0.5Sb0.5 nano-scale heterostructure under external uniaxial strain. (November 2017) - Singh, A.K.; Rathi, Amit; Riyaj, Md.; Bhardwaj, Garima; Alvi, P.A.
Abstract: Quaternary and ternary alloy semiconductors offer an extra degree of flexibility in terms of bandgap tuning. Modifications in the wave functions and alterations in optical transitions in quaternary and ternary QW (quantum well) heterostructures due to external uniaxial strain provide valuable insights on the characteristics of the heterostructure. This paper reports the optical gain in strained InGaAsP/GaAsSb type-II QW heterostructure (well width = 20 Å) under external uniaxial strain at room temperature (300 K). The entire heterostructure is supposed to be grown on InP substrate pseudomorphically. Band structure, wave functions, energy dispersion and momentum matrix elements of the heterostructure have been computed. 6 × 6 diagonalised k → · p → Hamiltonian matrix of the system is evaluated and Luttinger-Kohn model has been applied for the band structure and wavefunction calculations. TE mode optical gain spectrum in the QW-heterostructure under uniaxial strain along [110] is calculated. Optical gain of the heterostructure as a function of 2D carrier density and temperature variation is investigated. The variation of the peak optical gain as a function of As and Sb fractions in InGaAsP as a barrier and GaAsSb as a well respectively is exhibited. For a charge carrier injection of 5 × 10 12 / cm 2, the TE optical gain is 3952 cm − 1 at room temperature under no external uniaxial strain. Significant increase in TE mode optical gain is observed under high external uniaxial strain (1, 5 and 10 GPa) along [110] within IR (Infrared region) region. Highlights: Very high optical gain optimization in type-II InGaAsP/GaAsSb nano-scale heterostructure. Observation of optical gain under variable 2D carrier density injection and temperature. Significant improvement in interband optical gain by external uniaxial strain along [110]. Variation of the peak optical gain as a function of As and Sb fractions in InGaAsP as a barrier and GaAsSb QW respectively.